Judge's Legal Analysis of Murder Offices - Andi Istiqlal Assaad; M. Mursyid; S. Setyaningsih (Golden Ratio of Law and Social Policy Review (GRLSPR), 2021)
This study aims to describe the basis for the application of criminal law to the crime of murder that occurred in Wajo Regency and to find out the judge's considerations in making a decision on case Number 156/Pid.B/2020/PN.Sengkang through legal principles and legal norms that were taken into consideration. The research method that uses this case approach shows in the results of the study that the application of material punishment for the offense of murder is in accordance with applicable legal norms, all elements of criminal acts regulated in the applicable regulations in Indonesia have been met in which the defendant was sentenced to imprisonment for 14 (fourteen) years. twelve) years. The judge's legal considerations for the murder offense in the case were in accordance with the elements proven in the trial, so that the panel of judges based on the facts at trial judged that the defendant could be held accountable for his actions with the consideration that at the time he committed his actions the defendant was aware of the consequences and did not prevent him from doing so. the intention is that the perpetrator in carrying out his actions is in good health and capable of considering elements against the law, and there is no reason for the abolition of the crime.